The Management of Small Renal Masses Diagnosis and Management (Springer International Publishing, 2018)
Within this single volume, surgeons and medical students are able to find up-to-date clinical information and advice needed to manage this unique condition of small renal masses. The book aims to present information on the topic in a clear and logical way, with the help of figures, tables, and images that will assist in the practical application of the skills that are obtained from the book. The growth of new technologies and the continued development of existing techniques have led to a considerable number of new options that can be offered to patients by urologists. Despite these advances, challenges still remain and this book offers individual solutions to each aspect of the management of small renal masses, so that every diagnosis can be tailored to each patient. Written by leading experts, this book gives expert insight and advice into the diagnosing and managing of this condition. From making an accurate diagnosis to selecting the appropriate treatment for the patient, this book will provide a comprehensive guide on all aspects of the management of small renal masses.